Implementation of Portfolio Assessment in English Lessons at MAN Insan Cendekia Jambi - sultanuddin, sultanuddin; Saharudin, Saharudin; Yamin, Martinis; Waite, Vesna; Baral, Lekh Nath (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2023)
This research aims to: 1) obtain an overview of portfolio assessment planning for English language learning at MAN Insan Cendekia Jambi, 2) describe the implementation of portfolio assessment for English language learning at MAN Insan Cendekia Jambi. 3) describe the advantages and obstacles of portfolio assessment in English language learning at MAN Human Cendekia Jambi. The approach used in this research is qualitative research. The results of the research show that portfolio assessment planning in English language learning at MAN Insan Cendekia Jambi includes several components, such as: educator preparation, consideration of the values that will be applied, and determining appropriate learning material. Apart from that, the assessment also includes students' affective aspects which aim to form good student attitudes in accordance with the Islamic boarding school concept. The implementation of portfolio assessment in English language learning also experiences obstacles, namely limited time, different student characteristics, and institutional support regarding portfolio assessment that is not yet well systemized. Portfolio assessment in English language learning at MAN Insan Cendekia Jambi includes: evidence of thought processes, quality of activities, and diversity of approaches.The implementation of portfolio assessment in English lessons at MAN Insan Cendekia Jambi shows the school's commitment to improving students' learning experience holistically. This research has the potential to provide new insights regarding the effectiveness of alternative evaluation methods in the context of English language education.